MATHEMATICAL THEORY OF EVIDENCE TO DENGUE FEVER DETECTION - Andino Maseleno; Fauzi Fauzi; Muhammad Muslihudin (Jurusan Teknik Informatika, 2015)
This paper presents Dempster-Shafer Theory for dengue fever detection. Sustainable elimination of dengue fever as a public-health problem is feasible and requires continuous efforts and innovative approaches. In this research, we used Dempster-Shafer theory for detecting dengue fever diseasesand displaying the result of detection process. The Dempster-Shafer theory is a mathematical theory of evidence.Dengue fever diseases have the same symptoms withbabesiosis, lyme, malaria, and west nile. We describe six symptoms as major symptoms which include fever, red urine, skin rash, paralysis, headache, and arthritis. Dempster-Shafer theory to quantify the degree of belief, our approach uses Dempster-Shafer theory to combine beliefs under conditions of uncertainty and ignorance, and allows quantitative measurement of the belief and plausibility in our identification result.